CHARACTERISTICS OF TROPICAL STORMS AND STORM SURGES IN COASTAL ZONES OF VIETNAM - Co, Nguyen Thanh; Manh, Dinh Van (Vietnam Journal of Marine Science and Technology, 2018)
Tropical storms and storm surges are dangerous. The damage caused by them is very huge. Therefore, studying characteristics of storms and storm surges is of great interest today. This paper presents some study results on characteristics of tropical storms and storm surges, which landed in Vietnam during 1951-2015. These characteristics are determined based on the storm data collected on website of Japan Meteorological Agency, JMA. In the paper, the storm surges are calculated by a numerical model as TSIM 08 software. This softwave is established by the Institute of Mechanics, Vietnam Academy of Science and Technology. The numerical model has been calibrated and verified by measured storm surge data at the hydrographic, oceanographic stations along the Vietnam coast and the survey’s storm surge data in some storms.